EFFECTIVENESS OF MEDIATION IN RELIGIOUS COURTS - Suriani, Suriani; Rahmah, Mutia (Proceeding International Seminar of Islamic Studies, 2024)
The aim of this research is to determine the effectiveness of mediation in Religious Courts. Mediation is a form of dispute resolution process outside of court which is carried out either directly or electronically as regulated in Supreme Court Regulation (Perma) Number 1 of 2016 concerning Mediation Procedures in Court and Supreme Court Regulation (Perma) Number 3 of 2022 concerning Mediation In Court Electronically. This type of research is empirical research, namely research carried out directly or through field observations. Based on the research results, it is known that the Tanjung Balai Religious Court has carried out mediation in handling cases. In 2020, 72 cases were mediated, with 8 successful and 53 unsuccessful. In 2021, the number of cases mediated was 95, with details of 50 cases not being mediated, 16 successful and 29 unsuccessful. In 2022, the number of mediated cases will reach 180 cases, with details of 90 cases not suitable for mediation, then 7 cases were successfully mediated and 83 cases were unsuccessful. Based on this, it can be concluded that the implementation of mediation at the Tanjung Balai Religious Court has not been effective.